Domain-Specific Model-Driven Testing - Bärisch, Stefan. (Software Engineering Research, 2010)
Software reuse and software quality are increasingly important topics in today’s software engineering both for researchers and for practitioners. The design and implementation of tests is especially challenging when tests are conceptualized for different variants and versions of an application. Stefan Baerisch applies a combination of feature modelling and code generation, for which he uses a model-driven approach, in order to facilitate the design of tests by non-programmers. Thus, the reuse of tests, represented by abstract test models, for different systems under tests is made possible. The approach uses code generation to allow test execution on heterogeneous and changing implementations. This combination of modelling and code generation allows for a more integrated and more efficient testing process.